Pengaruh Kompensasi, Lingkungan Kerja, dan Work Family Conflict, terhadap Turnover Intention: The Influence of Compensation, Work Environment, and Work Family Conflict on Turnover Intention - Sevia Firdarani; Qristin Violinda; M.Fadjar Dharmaputra (Jurnal Kolaboratif Sains, 2024)
The purpose of this research is to determine the influence of compensation, work environment, and work family conflict on turnover intention of PT employees. Gitamadu Sweets Manufacturers Semarang. This type of research used in this research uses quantitative research methods. The population used is all employees of PT. Gitamadu Sweets Manufacturers Semarang, using saturated samples as a sampling technique. So the sample used in this research was 167 employees. Data analysis used in this research used multiple linear regression analysis with the help of the Statistical Package for the Social Sciences (SPSS) program. The research results show that the work environment influences turnover intention, there is no influence between the compensation variable and the work family conflict variable on turnover intention.